Productivity and condition of Austrian pine (Pinus nigra var. Austriaca Asch. et Gr.) in central and north-eastern parts of Ukraine - Tereshchenko, L. I.; Los, S. A.; Petrenko, M. I.; Samoday, V. P. (Forestry and Forest Melioration, 2019)
Introduction Austrian pine is naturally distributed in the Central Europe mountains, where it forms resistant stands at an altitude of 250–1,800 m. Due to environmental plasticity, Black pine is one of the most common species in forest regeneration worldwide. Thanks to its high ornamentality and resistance to air pollution, this species is widespread in parks and urban and industrial areas. The species was introduced into Ukraine about 200 years ago. Dobrovolsky recommended using it on richer types of sandy soils and sandy loams, transitional to clay-loams, for marginal pine forests with a small admixture of deciduous trees and shade-tolerant shrubs. The aim of the work was to characterize the Austrian pine stands of various ages of the first and second generations in Kirovohrad, Kharkiv and Sumy Regions and conduct a comprehensive assessment of their productivity, trunk quality and condition. Materials and methods Five Austrian pine stands were observed in Kirovohrad, Kharkiv and Sumy Regions during 2017–2018. The stands assessment was carried out based on the average height and diameter, an average tree volume, selection category, health category and reproduction. Mensuration variables were determined by generally accepted methods; both the selection category and the health category were defined according to the classification developed by the Laboratory of Forest Tree Breeding of URIFFM. Furthermore, the variability level of the growth indices was determined based on S. S. Mamayev scale. Growth rates of Austrian pine and Sсotсh pine were compared by means of Student’s test. Prospective viability of Austrian pine was determined according to a 3-point scale. Results In the State Enterprise “Oleksandrivske Forest Economy” in Kirovohrad Region in the fresh fairly infertile site, Austrian pine and Sсots pine grow according to the II productivity class. Austrian pine at the age of 117 reached the height of 26.5 m which was 6.4% shorter than the Scots pine. Moreover, its diameter was 32.7 cm and it was 19.9% less than that of Scots pine. The Student’s test showed that the diameter of Austrian pines is significantly less than that of Scots pines (tfact = 4.83, tSt = 1.98). The stands are normal by their selection structure; the trees of the second breeding category at the age of 117 made 14% of all trees. At that, more than half of the trees had straight trunks. Over the last 7 years, the stands’ health has worsened. Thus, the trees of excellent condition made 7% only. In severe steppe conditions in Veseli Bokovenky Dendrology Selection Forest Experemental Center, Kirovohrad Region, Austrian pine had an alley arrangement and was growing accoding to the VI productivity class. The average height of the 80–82-year-old trees was 17.2 m and their diameter was 28.1 cm. According to the yield tables, Austrian pine trees had 3% better height indices and 57.9% better diameter ones compared to Scots pine trees of the same age and productivity class. Most of the trees had straight trunks. The trees of I and II selection categories made 20.5%. At that, the share of minus trees was considerable, namely 36.4%. The trees of good and satisfactory conditions (73.3%) prevailed, 17.8% of trees had unsatisfactory condition. Almost all the trees had formed cones. The stand in Neskuchanske Forestry in the State Enterprise “Trostyanets Forest Economy” in Sumy Region in fresh fairly fertile site had the III productivity class. The height of 114-year-old Austrian pine trees ranged from 21.5 to 24.5 m, their diameter varied from 29.3 to 57.3 cm. Scots pine trees in this stand had the height from 22.5 to 25.0 m and diameter from 30.6 to 43.0 cm. Black pine had an average height which was 6.4% inferior to that of Sсots pine. However, its average diameter was 16.9% higher than that of Scotch pine. The Student’s test showed a significant difference (height tfact = 2.9, diameter tfact = 2.5, tSt = 2.04 at P = 0.95). In the State Enterprise “Kharkiv Forest Research Station” arboretum, in the fresh fertile site, where Austrian and Scots pines are planted as alleys, Austrian pine had the I productivity class and Scots pine Ia. Austrian pine had the height variation level twice as high as Scots pine (13.6% vs. 7.4%). The Scots pine trees with straight trunks made 25%, while only 16.7% of Scots trees had straight trunks. The analysis of the 27-year-old mix forest stand on eroded lands in the Oleksandrivske Forest Economy showed that the conservation status of Austrian pine was 33%; that of English oak was 35%. The growth of Scots pine in the fresh fairly fertile site corresponds to the 1B productivity class, the growth of the rest of the species – to the I class. The yield table data demonstrated that Scots pine trees were 9.4% higher and 56.6% wider in their diameter. At that, Austrian pine trees dropped 14.7% behind in their height and 1.0% in their diameter. Trees of the 1st selection category were only among Austrian pines (2.4%). The total share of trees of I and II categories were 26.1%. The proportion of trees of 2nd selection category was 18.2% for Scots pine and 13.8% for English oak. The comprehensive assessment of the studied stands provided the following data. Austrian pine scored more points than Scotch pine (3/4 cases) and the same number of points in the 27-year-old stand. Therefore, it is considered promising for planting forests and protective stands on eroded soils as well as for landscaping. Сonclusions Austrian pine drops behind Scotch pine by height in all studied stands, but in most of the cases it prevails by diameter, has higher-quality trunks and is of better condition. According to the results of the comprehensive assessment, Austrian pine has scored more or the same points with Scotch pine. Austrian pine is recognized as promising for planting forests and protective stands on eroded soils in central and north-eastern parts of Ukraine. Furthermore, with moderate recreational load it is able to perform ameliorative functions, and thanks to its high ornamentality it is promising for landscape gardening. To further introduce the species, it is necessary to expand the forest seed plantation base, namely: to select plus trees, to establish clonal and family seed plantations. At the present stage it is recommended to use the best stands for harvesting cones. 2 Figs., 3 Tables, 20 Refs.